Participatory Design as an Audiovisual Strategy in Brand Manuals - Borja Galeas, Carlos; Arias Flores, Hugo Patricio (My University, 2023)
The brand manuals serve so that the corporate image of a company is not distorted, when it is used in activities such as the design of advertising material. Designing a brand through participatory design allows accelerating and improving its development with new technologies. This study exposes a brand building model in which 96 companies registered at the National Institute of Popular and Solidarity Economy of the city of Quito participated. As a result of this research, the participants obtained the design of their logo and brand, based on their needs and the business in which they specialize. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.
Keywords: adaptive-range sensors; HEENS; Real-time sensor processing; Spike-rate filters; Spiking Neural Networks (SNNs)